Reengineering of culture institution as a potential breakthrough factor for an innovative region ("Journal "U". Economy. Management. Finance.", 2020)
Innovative potential of the region is subject to a number of conditions and factors that accelerate the innovation process. Interest in culture is very important for regions focused on innovative development, since the formation of the image of such a region includes opportunities for its socio-economic development and creates an investment-attractive environment. In this regard, the search for proposals to ensure the preservation of cultural heritage sites and the development of effective forms and methods of economic regulation of the development of the industry is of particular importance. The article suggests considering reengineering as the most advanced method for adapting real processes to rapidly changing conditions.
Keywords: innovation; region; culture institution; reengineering; factors of innovative potential of the region